1999
DOI: 10.1007/s11745-999-0418-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a dietary oxidized oil on lipid metabolism in rats

Abstract: This study was carried out to investigate the effects of a dietary oxidized oil on lipid metabolism in rats, particularly the desaturation of fatty acids. Two groups of rats were fed initially for a period of 35 d diets containing 10% of either fresh oil or thermally treated oil (150 degrees C, 6 d). The dietary fats used were markedly different for lipid peroxidation products (peroxide value: 94.5 vs. 3.1 meq O2/kg; thiobarbituric acid-reactive substances: 230 vs. 7 micromol/kg) but were equalized for their f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
57
0
6

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 34 publications
8
57
0
6
Order By: Relevance
“…Hochgraf et al (Hochgraf et al 1997) demonstrated that oxidized linoleic acid, which is present in sunflower seeds, promotes a significant increase in the plasma cholesterol levels in rats. In contrast, some other studies reported reduced levels of plasma cholesterol and triglycerides in rats and pigs in response to the consumption of oxidized dietary oil (Eder and Kirchgessner 1999;Eder 1999;Eder and Stangl 2000;Eder et al 2003;Acikgoz et al 2011). In this context, our results demonstrated increased cholesterol levels with HFD, which agrees with the proposed of Hochgraf et al (Hochgraf et al 1997).…”
Section: Discussionmentioning
confidence: 92%
“…Hochgraf et al (Hochgraf et al 1997) demonstrated that oxidized linoleic acid, which is present in sunflower seeds, promotes a significant increase in the plasma cholesterol levels in rats. In contrast, some other studies reported reduced levels of plasma cholesterol and triglycerides in rats and pigs in response to the consumption of oxidized dietary oil (Eder and Kirchgessner 1999;Eder 1999;Eder and Stangl 2000;Eder et al 2003;Acikgoz et al 2011). In this context, our results demonstrated increased cholesterol levels with HFD, which agrees with the proposed of Hochgraf et al (Hochgraf et al 1997).…”
Section: Discussionmentioning
confidence: 92%
“…It is very important to keep in our mind the relation between oil and lipids/energy metabolism. Koch et al 13) and Eder 14) showed that feeding thermally oxidized oils to rats caused a reduction in the concentration of triacylglycerols and cholesterol in liver and plasma. They explain that the reduction of triacylglycerols may be due to stimulation of hepatic b-oxidation triggered by activation of peroxisome proliferators-activated receptor a (PPARa) and reduced hepatic de novo fatty acid synthesis [15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…Koch et al 20) and Eder 21) showed that feeding thermally oxidized oils to rats caused a reduction in the concentrations of triacylglycerols and cholesterol in liver and plasma. They explain that the reduction of triacylglycerols may be due to stimulation of hepatic b-oxidation triggered by activation of peroxisome proliferators-activated receptor a (PPARa) and reduced hepatic de novo fatty acid synthesis [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%